Normative value of sensory nerve action potential of median and ulnar nerves: A cross-sectional study among healthy adults - Sunil Kumar Jena; Manoranjan Acharya (Wolters Kluwer Medknow Publications, 2022)
Background: Demographic factors such as age, height, weight, and body mass index are important to affect nerve conduction study. Hence, each neurology laboratory should establish its own normative reference data to evaluate the functional status of peripheral nerves. The aim of this study was to establish the normative value of sensory nerve action potential (SNAP) parameters of median and ulnar nerves. Materials and Methods: This study included 92 healthy adults (52 males and 40 females) between the age group of 20 and 60 years. They were classified into three groups A, B, and C. Body mass index was matched for the selection of study participants. SNAP was recorded as per the standard protocol and room temperature was maintained as per the standard guidelines. Onset latency (OL), amplitude (Amp), and conduction velocity (CV) were recorded for data analysis. One-way ANOVA and post hoc analysis were used for statistical analysis. P < 0.05 was considered to be statistically significant. Results: OL in the older age group was prolonged than younger both in the median and ulnar nerves. CV and Amp were less in the older age group than younger both in the median and ulnar nerves. The increasing tendency of OL was observed after 35 years of age. The decreasing tendency of Amp and CV was observed after 50 years of age. Conclusion: SNAP parameters vary according to demographic region. Hence, each laboratory should establish its own normative data to evaluate the functional status of peripheral nerves.